Detection, transmission and pathogenicity of fungi on Blepharocalyx salicifolius (H.B.K.) Berg. seeds - Rego,Suelen Santos (2012)
The objective of this study was to identify the fungi associated with the fruit and seeds of Blepharocalyx salicifolius and verify their transmission and pathogenicity to seeds and seedlings. Fungal identification on seeds was made using the blotter test and potato-dextrose-agar but only the blotter test was used for fruit. Fungal transmission to seedlings was evaluated using four replications of 50 seeds planted in vermiculite. The pathogenicity of the fungi, Colletotrichum sp., Curvularia sp., Cladosporium sp. Pestalotia sp. and Macrophomina sp. was tested. Potentially pathogenic and saprophytic fungi were found on the fruits and seeds. The transmission of Cladosporium sp. from seeds to seedlings was verified, and Cladosporium sp. Pestalotia sp. and Macrophomina sp. were found to be pathogenic to B. salicifolius seedlings.